Estrategias del marketing farmacéutico y las prescripciones del profesional de la salud en Lima 2019 - Pariñas Sánchez, Víctor Raúl (2022)
The objective of this article is to define the impact of pharmaceutical marketing strategies on the prescriptions of the Health Professional (HP) in Lima 2019. Pharmaceutical marketing refers to the strategies to promote brand products. Regarding the methodology, it is descriptive, correlational, cross-sectional and not experimental. Simple random probability sampling was used, these being 384 PS; all this compiled by means of a survey, resulting in a Cronbach's Alpha of 0.995; processed in the SPSS 26 Software, testing the hypothesis using the Chi Square statistic, this value being 1067.18 greater than the Critical Chi 16.919 and a Spearman correlation coefficient of 0.668 positive moderate, with a significance level of 0.000 being this lower than Critical 0.05, thus demonstrating that there is a high statistically significant difference between pharmaceutical marketing strategies and the prescription of HP in Lima in 2019.